Investment Opportunity Set as Moderation of Return on Assets and Debt to Equity Ratio to Stock Return - Purwanto, Eko Cahyo; Halim, Abdul; Muawanah, Umi (International Journal Labs, 2023)
This study aims to test and analyze: first the effect of ROA on RS, second the effect of DER on RS, third the influence of IOS on RS, fourth IOS moderating the effect of ROA on RS, fifth IOS moderating the effect of DER on RS. This research was conducted in property and real estate companies listed on the Indonesia Stock Exchange in 2020-2022, using an explanatory research approach, with purposive sampling techniques obtained by 63 companies. Secondary data in the form of research variables are collected by documentation methods in the form of financial statements via access to idx,. Co.Id, furthermore, were analyzed using moderation double linear regression. The results prove that: first, ROA has a significant positive effect on RS, second DER has a significant negative effect on RS, third IOS has a significant positive effect on RS, fourth IOS strengthens the influence of ROA on RS, fifth IOS strengthens the influence of DER on RS